Development of a Children's Version of the SCORE Index of Family Function and Change. Issue 4 (26th August 2013) - Jewell, Tom; Carr, Alan; Stratton, Peter; Lask, Judith; Eisler, Ivan
<x xml:space="preserve">Abstract</x> The Systemic Clinical Outcome and Routine Evaluation (SCORE) Index of Family Function and Change is a recently developed outcome measure. It was designed to be acceptable to adults and children aged 12 and over. Thus far no research has been conducted using the SCORE in children under the age of 12. The aim of this study was to pilot a children's version of the SCORE. An existing 29‐item version of the SCORE was completed by a sample of seven children aged 8–10. Time was allowed for group discussion with the children. Feedback from this stage of the study was used to develop a draft version of the SCORE for children. An expert panel of clinicians and researchers were also consulted. A pilot version of the Child SCORE was administered to 80 children aged 7–10 in an inner London primary school. Thirty‐five children also completed the measure for a second time, 1 week later. Findings suggested that the Child SCORE was acceptable to children in the 8–11 age range. Values for internal reliability and test–retest reliability were good. The Child SCORE appears to be a promising instrument. Further research is required to confirm its acceptability to clinical populations, and to demonstrate sensitivity to change.